The limits of structuralism forgotten sources in the history of modern linguistics - McElvenny, James ca. 20./21. Jh (Oxford University Press, 2023)
Based around seven primary texts spanning 130 years, this volume explores the conceptual boundaries of structuralism, a scholarly movement and associated body of doctrines foundational to modern linguistics and many other humanities and social sciences. Each chapter in the volume presents a classic — and yet today underappreciated — text that addresses questions crucial to the evolution of structuralism. The texts are made accessible to present-dayEnglish-speaking readers through translation and extensive critical notes; each text is also accompanied by a detailed introduction that places it in its intellectual and historical context and outlines the insights that it contains. The volume reveals the complex genealogy of our ideas and enriches our understandingof their contemporary form and use